EEG correlates of induced anxiety in obsessive-compulsive patients: comparison of autobiographical and general anxiety scenarios - Kamaradova, Dana; Brunovsky, Martin; Prasko, Jan; Horacek, Jiri; Hajda, Miroslav; Grambal, Ales; Latalova, Klara (Neuropsychiatric disease and treatment, 2018)
BACKGROUND: The underlying symptomatology of obsessive-compulsive disorder (OCD) can be viewed as an impairment in both cognitive and behavioral inhibition, regarding difficult inhibition of obsessions and behavioral compulsions. Converging results from neuroimaging and electroencephalographic (EEG) studies have identified changes in activities throughout the medial frontal and orbital cortex and subcortical structures supporting the cortico-striato-thalamo-cortical circuit model of OCD. This study aimed to elucidate the electrophysiological changes induced by autobiographical and general anxiety scenarios in patients with OCD. METHODS: Resting-state eyes-closed EEG data were recorded in 19 OCD patients and 15 healthy controls. Cortical EEG sources were estimated by standardized low-resolution electromagnetic tomography (sLORETA). The changes in the emotional state were induced by two different scenarios: the autobiographical script related to patient's OCD symptoms and the script triggering general anxiety. RESULTS: During the resting state, we proved increased delta activity in the frontal, limbic and temporal lobe and the sub-lobar area in OCD patients. In a comparison of neural activities during general anxiety in OCD patients and the control group, we proved an increase in delta (parietal, temporal, occipital, frontal and limbic lobes, and sub-lobal area), theta (temporal, parietal and occipital lobes) and alpha-1 activities (parietal lobe). Finally, we explored the neural activity of OCD patients during exposure to the autobiographic scenario. We proved an increase in beta-3 activity (left frontal lobe). CONCLUSION: Our study proved differences in neural activation in OCD patients and healthy controls during imagination of general anxiety. Exposure to the autobiographic OCD scenario leads to activation of left frontal brain areas. The results show the possibility of using specific scenarios in OCD therapy.
Keywords: electroencephalography; cognitive-behavior therapy; anxiety; obsessive–compulsive disorder; autobiographical script